Chaurasia's human anatomy for dental students : regional and applied anatomy, clinical applications, dissection - Chaurasia, B. D.; Garg, Krishna (New Delhi : CBS Pub., 2007)
HUMAN ANATOMY for Dental Students is based on the popular textbook BD Chaurasia`s Human Anatomy, volumes 1-3, and succinctly presents in one handy volume all the topics relevant to the BDS students, following the similar treatment of the subject - Regional and Applied Anatomy; Dissection and Clinical Applications. Gross anatomy of head and neck has been given in detail with dissection and illustrated clinical anatomy. Clinical terms form a separate heading to give them their due importance. Numerous radiographs, CT scans, MRI scans and ultrasound scans have been given to initiate the readers into the realm of radiology and imaging. The attachment of muscles and branches of arteries have been put in a tabular form. All the cranial nerves, parasympathetic ganglia, etc. are put in one chapter to make it more comprehensive. Steps of dissection have been put in blue boxes marked Dissection. The lines of skin incisions are shown in illustrations. The volume thus imparts both theoretical and practical knowledge to the readers. Clinicoanatomical problems and multiple choice questions have been incorporated to test the knowledge and skills acquired. The gross anatomy of the other five regions, namely, upper limb, thorax, brain, abdomen and pelvis, and lower limb, has been given4n respective sections. The attachments of the muscles in the respective chapters have been tabulated. Each section comprises chapters which are well illustrated with easily reproducible color diagrams. The clinical terms are the hallmark of this book - at the end of every section, important clinical terms are explained. This shall be a great help to the readers during their clinical years. . The last chapter of every section contains the course of nerves, arteries and their branches in tabulated form. The autonomic nerve supply of the various viscera and their effects are highlighted. The `crowning` feature of this book is the introduction of tables giving attachment of muscles, arteries and nerves for quick memorization. Printed Pages: 670.
Upper limb -- Thorax -- Head and neck -- Brain -- Abdomen and pelvis -- Lower limb.
Includes index.
Keywords: Human anatomy; Dental students; Human dissection